HOW IS THE SOCIAL STRATIFICATION SYSTEM SHAPED? - ŞAŞMAZ TEKEL, Suna (SSD Journal, 2025)
When we look at the history of humanity, it is seen that there is a stratification system in all types of societies. Social stratification involves hierarchical differences and inequalities. When relative possession or lack of possession of a social characteristic such as wealth or status becomes the principle of distribution for individuals in an unequal reward system, social differences begin to stratify in societies. Among sociological theories, the structural-functionalist theory sees the stratification system as necessary for the continuity of society, while Marxist theories criticize it in the context of inequalities. This article analyzes how social stratification is shaped within a society and then in the international order through sociological theories and ultimately examines the concept of global inequality.